Estrategias empleadas para el abordaje psicosocial de pacientes en rehabilitación post ACV desde el cuidado de enfermería. - Vargas Guzmán, James Duván; Campo Castiblanco, Karen Tatiana; Porrello Pinzón, Eimy Saraí (Universidad Antonio Nariño, 2023)
Chronic diseases are one of the greatest challenges for the health system in the world, as they are the major cause of morbidity and mortality and disability. Stroke is a chronic disabling disease that negatively impacts the quality of life of the sufferer and affects mental health by generating psychosocial symptoms.